COMPARATIVE STUDY OF FLEXIBLE PAVEMENT DESIGNS FOR NEW ROAD IN GREAT BRITAIN AND INDONESIA - Hanafi Basri (INFO-TEKNIK, 2009)
The objective of this article is to compare the design methods for flexible pavements for new roads and overlays between two countries, Great Britain and Indonesia.Pavement design procedures provide a structure that can be accepted in a specific environmental condition and able to satisfy the anticipated traffic loading. There are many factors influencing the thickness design of pavement, such as pavement materials, traffic load and climatic conditions, there is no doubt that the method of pavement design in one country may differ to another.This article reviews the design methods of flexible pavement for new roads in both countries. Simple comparative examples are presented together with discussion and comparision of the design methods. The results are then summarised in the concluding section.